OPTIMALISASI BELAJAR SISWA SD 3T: TOKEN ECONOMY BERBASIS TEORI BEHAVIORISTIK - Ellen Liana Nur Aisyah; M. Mamduh Winangun; Sri Usodoningtyas (JURNAL ILMIAH NUSANTARA, 2026)
The learning process of elementary school students in Indonesia's 3T (Tertinggal, Terluar, Termiskin) areas faces significant challenges due to low motivation and inadequate basic facilities, reflected by a PISA score of 366 and a 15.2% dropout rate. This study examines the application of Skinner's behavioristic theory through Token economy to optimize basic memorization and literacy skills. Employing a qualitative library research approach, the analysis synthesizes 17 sources spanning 1927-2026, focusing on positive reinforcement via weekly rewards of Rp2,000 per student. Problem formulations address (1) the absence of systematic reward systems in remote classrooms, and (2) inconsistent reinforcement of memorization behaviors. Objectives include designing a localized Token economy model and projecting a 20-point increase in simulated PISA scores within 6 months. Findings confirm behaviorism's 4% highest relevance for this context. Practical benefits provide implementation guidelines for 3T elementary teachers and policy recommendations for the Ministry of Education to save Rp120 billion in national dropout costs.